Calibration of the HP3 Radiometer on InSight. Issue 5 (26th May 2020) - Mueller, N. T.; Knollenberg, J.; Grott, M.; Kopp, E.; Walter, I.; Krause, C.; Hudson, T.; Spohn, T.; Smrekar, S.
Abstract: The Heatflow and Physical Properties Package (HP 3 ) radiometer is currently operating on Mars, observing two spots approximately 1 and 3 m north‐north‐west of the InSight lander. The instrument has primary sensors that are sensitive in the range of 8 to 14 μm and two more sensors with more narrow spectral ranges per field of view. The radiometer underwent radiometric and geometric calibration at DLR—Berlin; and on Mars radiometric self‐calibration is performed regularly. The self‐calibration confirms that one of the two primary sensors has been stable since the ground calibration, but environmental parameters that are likely associated with the thermal contact of sensor and instrument main body may have slightly changed. The other primary sensor has increased in sensitivity for an unknown reason but is still within expectation from the sensor design. The uncertainty of the two primary sensors is approximately 3 K at night, with somewhat larger errors in the late afternoon. This estimate includes the effect of sensitivity changes that would be too small to be reliably detected by the self‐calibration. Key Points: We describe the calibration of the HP 3 radiometer measuring surface brightness temperature on Mars next to the Insight lander Regular self‐calibration measurements on Mars ensure an uncertainty of 3 K at night